The causal correlation between gut microbiota abundance and pathogenesis of cervical cancer: a bidirectional mendelian randomization study - Yang, Hua (Frontiers in Microbiology, 2024)
Background: Observational studies and animal experiments suggested potential relevance between gut microbiota (GM) and cervical cancer (CC), but the relevance of this association remained to be clarified.We performed a two-sample bidirectional Mendelian randomization (MR) analysis to explore whether there was a causal correlation between GM and CC, and the direction of causality.In primary outcomes, we found that a higher abundance of class Clostridia, family Family XI, genus Alloprevotella, genus Ruminiclostridium 9, and order Clostridiales predicted higher risk of CC, and a higher abundance of class Lentisphaeria, family Acidaminococcaceae, genus Christensenellaceae R7 group, genus Marvinbryantia, order Victivallales, phylum Actinobacteria, and phylum Lentisphaerae predicted lower risk of CC. During verifiable outcomes, we found that a higher abundance of class Methanobacteria, family Actinomycetaceae, family Methanobacteriaceae, genus Lachnospiraceae UCG 010, genus Methanobrevibacter, order Actinomycetales, and order Methanobacteriales predicted a higher risk of CC, and a higher abundance of family Streptococcaceae, genus Dialister, and phylum Bacteroidetes predicted a lower risk of CC, and Vice versa.Our study implied a mutual causality between GM and CC, which provided a novel concept on the occurrence and development of CC, and might promote future functional or clinical analysis.